(untitled) (Current Horticulture, 2024)
Banana (Musa spp.) production is greatly influenced by weather parameters. Accurate weather based yield forecast helps planners and policy makers. Weather-based yield prediction models provide a trustworthy yield forecast, and also helps in forewarning of pest and diseases (Agrawal and Mehta, 2007). According to Salau et al., 2016 excessive rainfall and extremely high temperature can reduce banana productivity, while production is also small when both rainfall and temperature are very low with poor humidity. Information on yield climate relationship helps in forecasting yield and formulating suitable policies. Yield prediction or forecasting is an important aspect of developing economy so that proper planning can be undertaken for the sustainable growth.